Reduced Efficacy of Commercial Acaricides against Populations of Resistant Cattle Tick Rhipicephalus microplus from Two Municipalities of Antioquia, Colombia - Anderson Lopez-Arias; David Villar-Argaiz; Jenny J. Chaparro-Gutierrez; Robert J. Miller; Adalberto A. Perez De Leon (SAGE Publishing, 2014)
Two distant Antioquian cattle farms where systemic and topical acaricides had previously failed to control infestations by Rhipicephalus ( Boophilus) microplus were studied. An initial in vivo study was conducted using single subcutaneous injections with a long-acting formulation of ivermectin (630 μg/kg). Injections were made at 3-month intervals on animals at each farm to evaluate the therapeutic and persistent efficacy of ivermectin against R. microplus. Body tick counts and reproductive parameters of semi- or fully engorged females ≥5 mm) were assessed at 10-day intervals, and since no negative control group could be included, values were compared against those for day 0. Although there was an overall reduction of 50%-75% in tick numbers that persisted for 30-40 days, it was not significantly different at one of the farms and not enough to afford protection from severe infestations. The engorgement weight and egg mass weight of ticks from treated animals were significantly lower throughout the 50-day posttreatment period. Egg hatch was not significantly reduced posttreatment and remained at levels of 80%-90%. A random selection of 9 out of 28 commercial formulations of ivermectin sold in Colombia were analyzed by High Performance Liquid Chromatography (HPLC). All were within the expected labeled concentration (∓15% deviation) of 1% and 3.15% ivermectin except for one. A popular unregistered injectable widely used in both farms and labeled as "natural pyrethrin", was found to contain 10.5% ivermectin. An adult immersion test was conducted to evaluate the efficacy of topical acaricides to recommended concentrations of five commercial products and/or their combinations. Efficacy was determined by comparing the reproductive index of each treated group to that of the control group. Cypermethrin (150 ppm) was completely ineffective at both farms. Amitraz (208 ppm) exhibited low and intermediate efficacies of 14% and 56%. The combination of amitraz (100 ppm) and cypermethrin (150 ppm) was less efficacious than the amitraz alone. A generic product based on amitraz + citronella (208 ppm + 10 ppm, respectively) was shown to be less efficacious than the name-brand amitraz product. Products containing the organophosphate chlorpyrifos or trichlorfon exhibited intermediate efficacies of approximately 60% at the Tarso farm. We conclude that at these two locations, there is a high degree of resistance to many of the acaricides available in Colombia and confirm suspicions that ivermectin is no longer able to eliminate tick infestations.